Penguatan Literasi Mangrove di OKL SL bagi Keberlanjutan Ekologis Mangrove di Desa Debunaruk Kabupaten Malaka - Willem Amu Blegur; Krisantus Jumarto Tey Seran; Anastasia Kadek Dety Lestari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
The mangrove ecosystem is categorized into the coastal ecosystem to be recognized and preserved so that it can be functional for the community and the environment. The community of OKL Street Library is a community group that exists in the area of the Beibleka mangrove ecosystem, Debunaruk Village – Malaka. Unfortunately, this community group is not yet familiar with both this type of mangrove species and the size of the ecosystem. The community service proposed is entitled a mangrove literacy strengthening at OKL Street Library for mangrove ecological sustainability in Debunaruk Village in the District of Malaka. This activity is targeted at the active users of OKL Street Library. The objective of this activity is to increase the knowledge in understanding various species types of mangroves ecosystem. Direct observation using information technology applications, namely Google Earth and the internet. The point is to enhance positive perception and real action in preserving the mangrove ecosystem that provides ecological and economic benefits to the community of Debunaruk-Tahak, the Dsitrict of Malaka. The area size calculation employs Google Earth and the introduction of mangrove species using the internet, through which learners are introduced to technology-based applications. This activity is conducted hand in hand between the OKL Street Library and the community service staff, both in setting the problem focus and activity alternatives. OKL SL got improvement knowledge and skills about the type and usages of mangroves and the implementation of Google Earth. We helped them by sharing some books too for the students.